2022
DOI: 10.1002/nop2.1368
|View full text |Cite
|
Sign up to set email alerts
|

Nursing students' perceived stress, self‐efficacy, control and evaluation of a course in systematic clinical observation, physical assessment and decision‐making: An observational study in Norway

Abstract: Aim Simulation‐based nursing education interventions have a strong educational effect on psychomotoric skills, but students may experience physiological stress and anxiety during simulation. The aims of this study were to explore (1) nursing students' perceived stress, self‐efficacy, control and evaluation before and after simulation as part a structured course in physical assessment, (2) whether factors such as gender, age or previous work experience were associated with perceived stress during simulation and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
1
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 56 publications
(62 reference statements)
1
1
0
Order By: Relevance
“…This has clinical relevance because ANs are the ones that in Swedish healthcare spend most time bed-side with the patient. The increased level of self-confidence resonates with findings from Hansen et al [ 30 ], who in their evaluation of proACT training in nurse education found increased competence and feelings of security when assessing and managing acutely ill patients. The results also support findings from other interprofessional simulation-based initiatives in different hospital settings [ 31 34 ] and programs for healthcare students [ 35 ].…”
Section: Discussionsupporting
confidence: 75%
“…This has clinical relevance because ANs are the ones that in Swedish healthcare spend most time bed-side with the patient. The increased level of self-confidence resonates with findings from Hansen et al [ 30 ], who in their evaluation of proACT training in nurse education found increased competence and feelings of security when assessing and managing acutely ill patients. The results also support findings from other interprofessional simulation-based initiatives in different hospital settings [ 31 34 ] and programs for healthcare students [ 35 ].…”
Section: Discussionsupporting
confidence: 75%
“…A questionnaire was developed based on studies focusing on nursing students and nurses’ technical skills and self-assessed competence [ 26 , 27 , 28 , 29 ], as well as supervisors of nurse anesthetist students’ perspectives on clinical nursing experience as a prerequisite to the APN education [ 18 ]. Based on this, statements regarding the impact of clinical nursing experience on various aspects of nursing practice ( n = 15), perceived associations between APN students’ clinical nursing experience and the ability to achieve the learning outcomes in the APN education ( n = 3), and about the necessity of clinical nursing experience before entry to an APN education program ( n = 6) were developed.…”
Section: Methodsmentioning
confidence: 99%